The perceived impact of leadership coaching by branch managers at the First National Bank of Botswana - Otukile, Maureen Udah (My University, 2021)
This research examines the perceived impact of leadership coaching on the branch managers at the First National Bank of Botswana. It provides the foundation to investigate and understand whether coaching affects sustained behaviour change. It explores behaviour, attitudes and leadership effectiveness strategies and how the leadership coaching impacts them. In this, the researcher aimed at determining the perceived impact of leadership coaching on behaviour and attitudes; determining whether leadership coaching can impact leadership practices and establishing whether leadership coaching promotes leadership effectiveness strategies at the First National Bank of Botswana. The research used a qualitative research method to understand a phenomenon guided by the Theory of Planned Behaviour. Qualitative methods were chosen because of its nature of having a small sample size. The research adapted a case study since it is an empirical inquiry and case studies provide in-depth information that gives a detailed description of the phenomena. The main tool of data collection was a guided interview. The findings showed that leadership coaching positively impacts behaviour and attitude change needed for achieving their organisations’ objectives. Findings also showed that leaders who undergo leadership coaching are more likely to significantly contribute to better leadership practices like building adaptable cohesive teams, motivating team members to be engaged and maximizing the strengths and minimizing the weaknesses of subordinates. The research also found that leaders who complete a leadership coaching programme have better application of the leadership effectiveness strategies to help their teams achieve higher levels of self-efficacy
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Business and Executive Coaching), 2021
Keywords: Leadership; Leadership Coaching; Coaching Effectiveness; Attitudes; Behaviour; SDG-8: Decent work and economic growth